Analisis Kesesuaian Media NHK Easy News sebagai Fuku Kyouzai dalam Mata Kuliah Dokkai - Muhammad, Marshall Irsyad Bima; Saragih, Febi Ariani (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2024)
Teaching materials are needed as reinforcement material in order to fulfil the learning competence of students. This study aims to analyse the suitability of NHK Easy News Media in Todai Easy Japanese application as a companion teaching material in the 2005 revised Minna no Nihongo II book for N4 equivalent students. This research uses qualitative approach with descriptive qualitative method. The data sources were all vocabulary and grammar in Minna no Nihongo Shokyu II book and NHK Easy News media reading texts using the theory from Arikunto as a determinant of the suitability of these variables. The data collection techniques applied were observation, documentation study and questionnaires to two lecturers and 67 students. Then, to analyse the possibility of success of being accepted as a companion teaching material, using the theory from Aisyah et al. This analysis research shows that NHK media has 85% on vocabulary appropriateness and 98% on grammar appropriateness. These results indicate that NHK media are "very suitable" as companion teaching materials. This is reinforced by the responses given by lecturers and students, the majority of which gave answers and were positive on each statement. Keywords: dokkai; Fuku Kyouzai; teaching materials; Todai Easy Japanese.